Трансакційні витрати: сутність, класифікація та зв'язок з соціальним капіталом - Грицаєнко, Микола Ігорович; Грицаенко, Николай Игоревич; Hrytsaienko, Mykola (ТДАТУ, 2017)
UK: У статті на основі критичного опрацювання літературних джерел узагальнені різноманітні тра-ктування понять «соціальний капітал» та «трансакційні витрати», сформульовані їх авторські дефініції. Під-креслено важливу роль інституційного середовища у формуванні соціального капіталу, показаний взаємозв’язок соціального капіталу та трансакційних витрат. З метою подальшого використання у розробці методики оцінки трансакційних витрат розглянуті існуючі підходи та запропоноване власне бачення їх класифікації. EN: The main purpose of the article is to study the essence of transaction costs, their classification and definition of connection with social capital. Based on the critical study of literary sources, the author's definition of social capital as a set of able to bring income of ties and socio-economic relations that arise in a particular social network based on existing norms and trust are formulated. It is concluded that the ability of social capital to generate income is manifested in the reduction of specific transaction costs. In the article, the essence of transaction costs is considered as a set of costs that increase the price of the product without changing its consumer value arising as a result of the interaction of enterprises with other actors of the institu-tional environment. Transaction cost management requires an assessment, for which a classification is required. It is proposed to consider the classification of transaction costs by micro, mezzo and macro levels. Classification of transaction costs of the enterprise (micro level) is proposed to be considered as the cost of the transaction (information search costs, negoti-ation and contracting costs) and costs after the transaction (costs of specification and protection of property rights, costs of counteracting opportunistic behavior). In this case, the transaction costs of the industry (mezzo level) are proposed to be determined as the sum of transaction costs of the enterprises concerned; the transaction costs of the region (mezzo level) are estimated in the same way as the transaction costs of the national economy as a whole, for assessment of which (macro level) can be limited to the transactional sector of the economy. It is concluded that social capital allows establishing missing links, saving time for economic agents to find the right counterparties, and discussing the conditions for conducting transactions, increasing their frequency and diversity, thereby reducing specific transaction costs.
Transaction costs: satisfaction, classification and a connection with social capital
Keywords: інституційне середовище; капітал; соціальний капітал; трансакції; трансакційні витрати; класифікація трансакційних витрат; institutional environment; capital; social capital; transactions; transaction costs; classification of transaction costs